Management of IT-Based Innovative Learning Training in Enhancing Teachers’ Pedagogical Competence - Yutarsih Yutarsih; Ahmad Sukandar (Journal of Science and Education (JSE), 2026)
This study provides an in-depth evaluation of the management of innovative IT-based learning training designed to enhance the pedagogical competence of teachers at the primary school level. Motivated by the critical academic concern regarding the persistent gap between the demands of modern digital pedagogy and the conventional teaching methods still widely used, this research critically examines how a systematically designed training program can serve as a concrete solution. Adopting a descriptive qualitative approach with a double case study design focusing on SDN Kutawaringin and SDN Cibalandongan, comprehensive data was collected through triangulation (in-depth interviews, participatory observation, and detailed documentation analysis). The findings consistently show that the training management at both schools was highly effective and well-organized, validated through systematic planning, meticulous organization, efficient implementation, and rigorous control. This success surpasses the mere adherence to G.R. Terry's management theory and aligns with professional mandates such as Law Number 14 of 2005 concerning Teachers and Lecturers. The improvement in teachers' pedagogical competence is evidenced by a real and measurable behavioral change, where teachers proactively integrate information technology (IT) into the entire teaching and learning process (e.g., using Google Classroom, Canva, and interactive quizzes). Therefore, this study concludes that structured, comprehensive, and data-driven training management is the main key to success in improving teachers' professional competence and effectively fostering a more innovative and sustainable learning culture within the school environment. The study offers an empirically tested model for replication by other educational institutions.